Refresing dan Evaluasi Monitoring Kader dan Keluarga dalam Perawatan ODGJ dengan Model Kelurahan Peduli Sehat Jiwa Dikota Semarang - Sri Endang Windiarti; Nurisda Eva Irmawati; Dian Tri Utami (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The prevalence of mental disorders in Indonesia reached 1.8 per mile, with Central Java at 2.5 per mile, ranking fourth after the Special Regions of Yogyakarta, Bali, and West Nusa Tenggara. In Semarang City, the prevalence of severe mental disorders is recorded at 1.1 per mile (Health, 2018). The high rate of recurrence at the dr. Aminogondo Hutomo Mental Hospital Semarang shows that the stigma against mental disorders is still strong, so the quality of life of sufferers remains low. This is exacerbated by the lack of awareness among families and communities that people with mental disorders need full support from the environment. To answer these challenges, the Peduli Sehat Jiwa Village model was developed as a community-based health service program. This program involves interventions in the form of mental health knowledge refreshment for families, community leaders, cadres, and health workers; the establishment of a health working group; mental health cadre training; as well as assistance to the families of the sufferer. The main focus is directed on non-communicable diseases, in particular schizophrenia. The hope of this community service is to reduce the rate of recurrence, reduce the burden on families and the government, increase public awareness of mental health, and suppress the emergence of new cases. With a participatory approach, this program is expected to be able to reduce stigma and improve the quality of life of people with mental disorders in a sustainable manner.